Effects of pepsoygen and dried porcine solubles 50 in nursery pig diets - Jones, C.K.; DeRouchey, Joel M.; Nelssen, Jim L.; Tokach, Michael D.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Two experiments were conducted to evaluate the effects of dietary specialty protein source on weanling pig growth performance. In Exp. 1, 350 pigs (initially 13.4 lb) were used in a 35-d growth trial to compare the effects of fish meal, PepSoyGen, and dried porcine solubles (DPS 50) on weanling pig performance. Seven dietary treatments were fed: (1) negative control, (2) 3% fish meal, (3) 6% fish meal, (4) 3.75% PepSoyGen, (5) 7.50% PepSoyGen, (6) 1.88% PepSoyGen and 1.88% DPS 50, and (7) 3.75% PepSoyGen and 3.75% DPS 50. From d 0 to 14, pigs fed increasing PepSoyGen and PepSoyGen in combination with DPS 50 had improved (quadratic, P = 0.01, linear, P = 0.002, respectively) F/G. Average daily gain and F/G were improved (P = 0.05 and P = 0.03, respectively) for pigs fed diets containing PepSoyGen and DPS 50 combinations compared with pigs fed diets containing fish meal. Also, feeding the combination of PepSoyGen and DPS 50 improved ADG and ADFI (P = 0.01 and P = 0.02, respectively) compared with feeding only PepSoyGen. Overall (d 0 to 35), pigs fed increasing PepSoyGen from d 0 to 14 had improved F/G (quadratic, P = 0.03). In Exp. 2, 252 pigs (initially 15.0 lb) were used to evaluate the effects of fish meal, PepSoyGen, and DPS 50 on nursery pig performance. A common pelleted starter diet was fed from weaning until the start of the experiment (d 7). Six dietary treatments were fed: (1) negative control, (2) 5% fish meal, (3) 3.5% DPS 50, (4) 6.0% PepSoyGen, (5) 1.75% PepSoyGen and 1.75% DPS 50, and (6) 3.0% PepSoyGen and 2.5% fish meal. During the treatment period (d 0 to 14), pigs fed DPS 50 alone or in combination with PepSoyGen had improved ADG and F/G (P < 0.05) compared with pigs fed all other diets. Overall (d 0 to 28), pigs fed DPS 50 from d 0 to 14 had improved ADG and F/G (P < 0.05) compared with pigs fed the control diet. Additionally, pigs fed DPS 50 had improved F/G (P < 0.05) compared with pigs fed PepSoyGen and fish meal in combination. In conclusion, pigs fed DPS 50 alone or in combination with PepSoyGen had improved performance compared with pigs fed the control diet.
Keywords: Growth; Nursery pig; Protein sources